Dampak Pandemi Covid-19 Terhadap Pengangguran serta Jabatan Kerja Kritis - Dewi Eva Kiranti; Lucky Nugroho (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
The current global phenomenon is the occurrence of the Covid-19 pandemic that affects all sectors, including the world of employment. Policies related to health protocols (keeping your distance, maintaining personal hygiene, the use of masks) and mobility restrictions have changed Indonesia's employment map. On the other hand, the phenomenon of the development of the industrial revolution 4.0 became faster to develop due to the need for business and financial transaction mechanisms during the Covid-19 pandemic that mitigated transactions physically. Therefore, this study is a literature study aimed at analyzing the impact of the Covid-19 pandemic on the number of unemployed and position trends during the Covid-19 pandemic and after the Covid-19 pandemic. The method used is qualitative, which discusses the formulation of problems descriptively supported by previous research and information sources in the form of data reports published by the competent authorities in Indonesia, namely the Ministry of Manpower. As for the formulations of the problems in this study: (i) How the number of unemployed during the Covid-19 pandemic; (ii) How the employment position trend during the Covid-19 pandemic. Furthermore, the result of this study is a significant increase in unemployment during the Covid-19 pandemic, and it is known that there are 35 critical categories of professions affected by the Covid-19 pandemic. The implications of this study are as information to job seekers and add scientific characteristics for both academics and practitioners in the field of employment